FOOD AND NUTRITION SECURITY, GENDER AND EDUCATION: AN INTEGRATIVE APPROACH - Jussara Maysa Silva Campos; Rita de Cássia de Almeida Coelho Akutsu (Universidade do Estado do Rio de Janeiro, 2016)
In view of women's role for food and nutrition security, as well as the interference of socioeconomic elements, such as education, this current research presents an integrative review of these issues. It is a bibliographical integrative review which presents scientific publications from ScienceDirect® and SciELO® databases, from 2004 to 2014, about "food and nutrition security and gender" and "food and nutrition security and education" themes (in Portuguese and English languages), regarding the identification of the approach of the mentioned ones. The selected publications follow the principles of integrative investigation taking into account: key word quotes on the title of the articles, the average rate of impact factors from 2004 to 2013 and the publication year. Subsequently, the main emerged themes on the selected publications were categorized. The analysis of the published contents considered their convergences or divergences among other national and/or international data. It is concluded that the selected publications ratified the Brazilian advances in Human Right to Adequate Food, and in spite of the major feminine vulnerability (and the families headed by them) to food insecurity, the female contribution on the food and nutrition security promotion is undeniable, either in Brazil and in the world. It also highlights the relevance of the development of other research on the "food and nutrition security and Education" issue on the perspective of educational and emancipatory processes, and traditional nutritional education related to the promotion of healthy habits as well. The importance of Brazilian studies that relate "food and nutrition security and gender" was also identified, especially with the objective of helping the promotion of equity in these relations, increasing female roles for food and nutrition safety. DOI: 10.12957/demetra.2016.22517